On Land/scapes (Performance Research, 2025)
<p style="margin: 0px; font-style: normal; font-variant-caps: normal; font-stretch: normal; font-size: 12px; line-height: normal; font-family: Arial; font-size-adjust: none; font-kerning: auto; font-variant-alternates: normal; font-variant-ligatures: normal; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-position: normal; font-variant-emoji: normal; font-feature-settings: normal; font-optical-sizing: auto; font-variation-settings: normal;">Call for Proposals <p style="margin: 0px; font-style: normal; font-variant-caps: normal; font-stretch: normal; font-size: 12px; line-height: normal; font-family: Arial; font-size-adjust: none; font-kerning: auto; font-variant-alternates: normal; font-variant-ligatures: normal; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-position: normal; font-variant-emoji: normal; font-feature-settings: normal; font-optical-sizing: auto; font-variation-settings: normal;">Vol. 30, No. 4 – ‘On Land/scapes’ (June 2025) <p style="margin: 0px; font-style: normal; font-variant-caps: normal; font-stretch: normal; font-size: 12px; line-height: normal; font-family: Arial; font-size-adjust: none; font-kerning: auto; font-variant-alternates: normal; font-variant-ligatures: normal; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-position: normal; font-variant-emoji: normal; font-feature-settings: normal; font-optical-sizing: auto; font-variation-settings: normal;">Proposal Deadline: 7 December 2024 <p style="margin: 0px; font-style: normal; font-variant-caps: normal; font-stretch: normal; font-size: 12px; line-height: normal; font-family: Arial; font-size-adjust: none; font-kerning: auto; font-variant-alternates: normal; font-variant-ligatures: normal; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-position: normal; font-variant-emoji: normal; font-feature-settings: normal; font-optical-sizing: auto; font-variation-settings: normal;">Issue Editors: Gigi Argyropoulou (Lund University, Sweden), Peader Kirk (Manchester <p style="margin: 0px; font-style: normal; font-variant-caps: normal; font-stretch: normal; font-size: 12px; line-height: normal; font-family: Arial; font-size-adjust: none; font-kerning: auto; font-variant-alternates: normal; font-variant-ligatures: normal; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-position: normal; font-variant-emoji: normal; font-feature-settings: normal; font-optical-sizing: auto; font-variation-settings: normal;">Metropolitan University, UK), Aparna Nambiar (Davidson College, USA) This issue proposes a focus on land/scapes as urgent and productive for discussing, analysing and making performance today. Land/scapes are considered as an active element and as a focal point for understanding emergent practices at the intersection of politics, ecology and performance. To think with/On Land/scapes is to challenge the hierarchies of a linear understanding and the validity of an external point of view. Being in and On Land/scapes means recognizing ways of making that challenge the means of domination, and to institute modes of doing and thinking that recognize dependencies. As Éduard Glissant (2021) notes: The earth is trembling. Systems of thought have been demolished, and there are no more straight paths. There are endless floods, eruptions, earthquakes, fires. Today, the world is unpredictable and in such a world, utopia is necessary. But utopia needs trembling thinking: we cannot discuss utopia with fixed ideas. (Glissant 2021) By emphasizing dense interconnections, entanglements and interdependencies in land/scapes, this issue seeks to explore ways of knowing and studying in and with the body and in relation to shaping and being shaped by the land/scapes we inhabit. Following Jane Bennett (2010) we ask: What are the political implications of recognizing that everything – including rocks, landfills and spools of thread – is alive in the landscape? We begin this exploration by looking at an etymological misunderstanding relating to the word ‘landscape’ that seems particularly fruitful for performance studies. Landscape, as Tim Ingold points out, derives from the Dutch word landscap, initially referring to an ‘area of land bound into … everyday practices’ (2021: 126), but as the term was incorporated into the language of painterly depiction led to a confusion between scape and scope. ‘Scope’ comes from the classical Greek skopos from which is derived the verb skopein, ‘to look.’ ‘Scape,’ to the contrary, comes from Old English sceppan or skyppan, meaning ‘to shape.’ Medieval shapers of the land were not painters but farmers, whose purpose was not to render the material world in appearance rather than substance, but to wrest a living from the earth. (Ingold 2021: 127) Seeking to elaborate the tension between scaped with the scopic, looking and shaping, this issue examines the ways that socio-political, cultural and ecological landscapes are mutually interconnected. Isn’t ‘looking’ often a ‘shaping’ and ‘shaping’ an attempt to materialize other ways of ‘looking’? How might ‘response-ability’ (Haraway 2016) offer new modes of practice and situatedness in, with and against sedimented practices in the landscape? (Sedimented practices being power relations that shape society, its embedded governmental relations, routinized forms of exploitation and violence, normative forms of cultural practice and thought.) How might such practices make visible the politics of the landscape or even help to shape new social habits and pedagogies of common? This misunderstanding between looking or witnessing and shaping or instituting otherwise seems particularly fruitful as we seek to discuss the myriad ways performance practice and methods relate to ecological and political conditions today. Land/scaping practices considered in this issue might include those shaped by human intervention such as: bordering practices to mark sovereign territory, camp or ‘no-man’s-land’; segmentation of land as a productive and unproductive space; articulation of land as grounds for national and communal identity; and eco-bureaucratic markings of land as wild or gardened spaces. In addition to this, non-human agential action of shaping land through natural phenomena, as well as the rehabilitating, reclaiming or resuscitating of land from nature for human ends, may also be considered as land/scaping practices. Laura Harris (2022) asks whether land can be discovered and defended without be- ing settled in her discussion of the work of Barbadian poet and historiographer Kamau Brathwaite. For Brathwaite the landscape comprises a deep sense of attachment, in his attempt to find ‘the language … w/which to write the poetry … which will recover the language of the land – the landuage – of the landscape … its uses & beauty, its magical reality’ (cited in Harris 2022: 33). Can the ‘landuage’ of the landscape be found in between skoppein and scappen, witnessing, shaping and being shaped? Can an engagement with the land/scape offer other ways of relating and thus other ways of being in the world? How might communal and embodied ways to be ‘in and with the land’, as Leanne Betasamosake Simpson (2014) argues, where ‘land, aki, is both the context and the process’, help us think towards decolonized futures? Can an entanglement with the land/scape offer ways to exercise what Glissant calls trembling thinking’ (and doing)? In what ways might performance practice shape and be shaped by sociopolitical and cultural land/scapes? How might this trembling thinking that happens in and with the landscape offer new para- digms of performance practice that engage/undo/challenge/overflow the politics of land/scape? Building on histories of performance in relation to land, space, location, publics and the environment this issue explores questions of relevance, situatedness, groundation, re-wilding, sedimentation, response-ability, destruction, intervention, wayfinding, instituting otherwise, symbiosis and persistence. We invite a wide range of contributions to embrace this multi-disciplinary focus. Possible topics include, but are by no means limited to, the following:  writing, thinking, making in and with the landscape  landscapes in crisis, dystopia, destruction  dramaturgies of the landscape  landscape and practices of symbiosis  curating in/with landscapes.  site-specific practice and performance situatedness in relation to the land- scape  interventions and making performance in relation to social, political and eco- logical landscapes  politics of the location, ancestral practices and situated knowledges  decolonializing landscapes  wayfinding, mapping, critical walking practices and the landscape  performing landscapes and posthuman thought  theatre, remains and climate crisis  queer and feminist landscapes  settler colonialism landscapes and practices of resistance  necropolitics, dispossession and landscapes of mourning  ecologies of belonging, participation and landscapes in the making  indigenous landscapes and politics of exclusion/inclusion  repair, waste and art practices in the landscape As we attempt to think in and with current land/scapes we encourage contributions interested in exploring, following Fred Moten (2023), practices of collective study that seek to ‘renew and redefine our anticolonial practices’ from wherever we are. We welcome articles that think through issues of contemporary, international, geopolitical significance in relation to land, its shaping and scoping. References Bennett, Jane (2010) Vibrant Matters: A political ecology of things, Durham, NC: Duke University Press. Glissant, Éduard (2021) ‘In conversation with Hans Ulrich Obrist’, https://bit.ly/4h39ztW, accessed 20 September 2024. Haraway, Donna (2016) Staying with the Trouble: Making kin in the Chthulucene, Durham, NC: Duke University Press. Harris, Laura (2022) ‘On groundation: Kamau Brathwaite’s CowPastor poems’, in G. Argyropoulou (ed.) Instituting: Space-making, refusal and organising in the arts and beyond, Berlin: Archive books, pp. 28–51. Ingold, Tim (2021) ‘Landscape or weather-world?’, in Being Alive: Essays on movement, knowledge, and description, London: Routledge, pp. 126–7. Moten, Fred (2023) ‘A dam against the motion of history’, https://bit.ly/482D1vL , accessed 20 September 2024. Simpson, Leanne Betasamosake (2014) ‘Land as pedagogy: Nishnaabeg intelligence and rebellious transformation’, Decolonization: Indigeneity, education & society 3(3): 1–25.